Responses of human adipose-derived stem cells to interstitial level of extremely low shear flows regarding differentiation, morphology, and proliferation. Issue 12 (25th May 2017) - Kim, Sung-Hwan; Ahn, Kihoon; Park, Joong Yull
Abstract : We developed a shear stress-gradient chip, which mimicked in vivo interstitial level of flow. With this system, hASCs' quantitative responses to the interstitial level of shear flow are identified. Abstract : Human cells encounter a range of shear stress levels in situ and this natural variability in shear stress implies that realistic investigations of cell type characteristics may depend on nontrivial shear stress models. Human adipose-derived stem cells (hASCs) differentiate near the blood capillary vessels where interstitial flows predominate. However, the effects of interstitial levels of shear on hASCs are not fully understood. In this study, we propose a microfluidic shear generation system, in which a gradient distribution of the interstitial level of shear flow is created to investigate the effects of interstitial-level shear flow on hASCs. To generate such a gradient profile of interstitial-level shear stress, we fabricated a semicircle-shaped microfluidic channel, and generated an extremely low flow using an osmosis-driven pump. Changes to hASC morphology, proliferation, and differentiation were observed under shear stresses of 1.8 × 10 −3 –2.4 × 10 −3 Pa. At higher shear stresses, we found higher proliferation rates, stronger actin structures, and lower differentiation. We also conducted computational simulations of a monolayer culture, which showed that the shear stress level even on a single cell varies owing to the change of the cell thickness between the pseudopodia and the nucleus. We found that hASCs detectably respond to extremely low levels of shear flow, above a threshold of ∼2.0 × 10 −3 Pa. Our microplatform may be useful for quantitating biological responses and function changes of other stem cells and cancer cells to interstitial-level shear flows.